KEBUDAYAAN MEGALITIKUM SEBAGAI OBJEK WISATA SEJARAH DI HUTA SIALLAGAN KECAMATAN SIMANINDO KABUPATEN SAMOSIR - R, Debora Natalia; Isjoni, Isjoni; Tugiman, Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Megalithic culture in Huta Siallagan District Simanindo Samosir Regency is one of the historical attractions that has its own uniqueness. The megalithic culture in Huta Siallagan is a cultural heritage of Batak people regarding community activities in the past. This is evidence of the historical legacy of the culture of the Batak people in the form of the megalithic tradition. The purpose of this study is 1) to know the function of megalithic culture in Huta Siallagan in the past, 2) the use of megalithic culture in Huta Siallagan in the present, 3) the role of the government in maintaining megalithic culture in Huta Siallagan, 4) tourist perceptions of megalithic culture at Huta Siallagan. The method used is a combination method, which is a research method that combines or combines quantitative methods with qualitative methods, and data collection techniques in the form of interviews, literature, observation, documentation. The result of this study are that the megalithic culture in th Huta Siallagan are stone chair and table which functions as a meeting place or decides everything, whether on social matters, customary law, or to decide criminal cases. Megalithic culture in Huta Siallagan in the present has now been used as one of the tourist attractions on Samosir Island which is visited by many tourists. To maintain and develop this tourism, yhe government carries out several policies, namely by channeling sufficient accessibility, and the availability of adequate facilities and infrastructure.Key Words: Culture, Megalithic, Huta Siallagan, Samosir.